2019
DOI: 10.1002/bdr2.1558
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey regarding the life situations of patients with thalidomide embryopathy in Japan, 2018: First report

Abstract: Background: Clinical studies on the effects of thalidomide-induced damage on thalidomide victims as they age have only recently started to be conducted, but no studies have examined socioeconomic differences in terms of healthcare and social status between thalidomiders and the age-matched general population in Japan. Therefore, we carried out a nationwide survey focusing on the life situations of thalidomiders. Method: Questionnaires were sent to 274 thalidomiders in Japan. The questionnaire items basically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In contrast, other studies found a doubled rate of psychological disorders, including anxiety, worries and stress (Hinoshita et al. 2019; Kowalski et al., 2015).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, other studies found a doubled rate of psychological disorders, including anxiety, worries and stress (Hinoshita et al. 2019; Kowalski et al., 2015).…”
mentioning
confidence: 77%
“…In contrast, other studies found a doubled rate of psychological disorders, including anxiety, worries and stress (Hinoshita et al 2019;Kowalski et al, 2015). Chronic pain disorders have recently been found in 94% of over 50-year-olds with TE (Niecke et al, 2022).…”
mentioning
confidence: 89%
“…The most common presentations are pain, increasing restriction with activities of daily living and nerve-related symptoms, particularly carpal tunnel syndrome ( Ohnishi and Hinoshita, 2017 ). The assessment focuses on the history of the presenting symptoms while taking into account how this affects their broader function, as pain and decreasing joint movement owing to new onset adult symptoms compound existing impairments ( Newbronner and Atkin, 2018 ).…”
Section: Management Of the Adult Patientmentioning
confidence: 99%
“…About 3,000–4,000 thalidomide survivors live around the world (Hinoshita et al, 2019), 773 of them in North Rhine‐Westphalia (NRW) in Germany. Today, they undergo secondary diseases as long‐term sequelae of their prenatal acquired impairments (Niecke, n.d.; Newbronner & Atkin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, thalidomide embryopathy is not only a medical care issue for aging subjects in the northern hemisphere but also a present health threat for young families in the southern hemisphere (Weinrich et al, 2018). About 3,000-4,000 thalidomide survivors live around the world (Hinoshita et al, 2019), 773 of them in North Rhine-Westphalia (NRW) in Germany. Today, they undergo secondary diseases as long-term sequelae of their prenatal acquired impairments (Niecke, n.d.;Newbronner & Atkin, 2018).…”
Section: Introductionmentioning
confidence: 99%